Recent progress in analyzing the spatial structure of the human microbiome: Distinguishing biogeography and architecture in the oral and gut communities. (June 2021) - Adade, Emmanuel E.; Al Lakhen, Khalid; Lemus, Alex A.; Valm, Alex M.
Abstract: Fueled by technological advances in methods for sample collection and preservation in sequencing studies and in advances in computational analyses of high-content image data, the spatial structure of the human microbiome is coming to light. In this mini-review, we summarize recent developments in our understanding of the structure of two human microbiomes: the lower gut and the oral cavity. We focus on only the most recent literature, and we make an important distinction between two forms of spatial structure governed by scale: biogeography and architecture. By segmenting the study of microbiome spatial structure into two categories, we demonstrate the potential to greatly advance our understanding of the mechanistic principles that link structure and function in the microbiome. Highlights: Microbiome biogeography and architecture may be considered two kinds of structure governed by scale. Analysis of microbiome spatial structure is fostered by new and developing technologies. Non shedding teeth support more complex biofilms than shedding epithelia. Microbiome architecture is studied with an ecological and cell biological perspective.